Dependence of Technetium-99m Radioactivity on the Stability of Tc-99m Tetrofosmin as Injectable Radiopharmaceuticals - Widyastuti Widjaksana; Puji Widayati; Yunilda Alwi; Lindawati N (The Journal of Pure and Applied Chemistry Research, 2018)
Technetium-99m (Tc-99m) labeled tetrofosmin kit has been widely used in hospitals including in Indonesia. Usually, tetrofosmin kits and Tc-99m pertechnetate are supplied separately, but recently there has been a new trend where Tc-99m tetrofosmin is supplied in the form of the ready-to-inject product. To prepare such a product it has to be proven that tetrofosmin can be labeled with high activity of Tc-99m and the resulted Tc-99m tetrofosmin, remains stable within shipping time until being used in hospitals. In this investigation, locally produced tetrofosmin kits were labeled with various radioactivity of Tc-99m ranging from 150 mCi to 400 mCi, their radiolabeling yields or radiochemical purity was analyzed using SepPak C18 column, and the radiochemical stability was assessed within 30 hours. The worst storage condition was also studied by analyzing its radiochemical purity after being stored at extreme temperatures for several hours. The results showed that tetrofosmin kit can be highly labeled with up to 415 mCi of Tc-99m, and stable up to 30 hours in room temperature, and there is a tendency that higher radioactivity leads to more decreasing in radiochemical purity. Stability study in extreme temperatures showed that the product can withstand its stability within 6 hours in 40°C, but it decreased rapidly to less than 70% within 1 hour when stored in 50°C. It concludes that the quality of Tc-99m tetrofosmin as an injectable radiopharmaceutical can be maintained during transportation by storing it at cool temperature.